2013
DOI: 10.1007/s00344-013-9322-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water-Deficit Irrigation on Hormonal Content and Nitrogen Compounds in Developing Berries of Vitis vinifera L. cv. Tempranillo

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…The decreased IAA levels observed under severe drought may result from the effect of water deficit on IAA polar transportation41. Studies with different crops have shown increased ABA and decreased IAA levels under osmotic stress due to drought or salinity stress4344. Here, increased ABA and decreased IAA concentrations were observed under severe drought for all plant combinations.…”
Section: Discussionmentioning
confidence: 73%
“…The decreased IAA levels observed under severe drought may result from the effect of water deficit on IAA polar transportation41. Studies with different crops have shown increased ABA and decreased IAA levels under osmotic stress due to drought or salinity stress4344. Here, increased ABA and decreased IAA concentrations were observed under severe drought for all plant combinations.…”
Section: Discussionmentioning
confidence: 73%
“…ABA is a key signal in the trigger of berry ripening, as suggested by the increase of berry ABA content around véraison (Wheeler et al, 2009; Giribaldi et al, 2010; Sun et al, 2010; Zifkin et al, 2012; Karppinen et al, 2013; Niculcea et al, 2013). However, the effect of water stress on ABA concentration in grape berries is far from being conclusively addressed (Deluc et al, 2009; Balint and Reynolds, 2013; Niculcea et al, 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of water stress on ABA concentration in grape berries is far from being conclusively addressed (Deluc et al, 2009; Balint and Reynolds, 2013; Niculcea et al, 2013, 2014). In addition, contrasting findings have been reported in studies exploring the effect of heat stress on ABA metabolism (Azuma et al, 2012; Carbonell-Bejerano et al, 2013; Rienth et al, 2014) which appear to be particularly dependent on grape berry phenology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, detailed information about the variation in ABA metabolites and other phytohormones in climbing plants is scarce (Balint and Reynolds 2013;Niculcea et al 2013). In this context, the stems of hop (Humulus lupulus L.) plants are not only long (up to 12 m), but also annual and exhibit rapid growth similarly to small herbaceous plants.…”
Section: Introductionmentioning
confidence: 98%